2016
DOI: 10.1042/cs20160433
|View full text |Cite
|
Sign up to set email alerts
|

APOA5 genetic and epigenetic variability jointly regulate circulating triacylglycerol levels

Abstract: Apolipoprotein A5 gene (APOA5) variability explains part of the individual's predisposition to hypertriacylglycerolaemia (HTG). Such predisposition has an inherited component (polymorphisms) and an acquired component regulated by the environment (epigenetic modifications). We hypothesize that the integrated analysis of both components will improve our capacity to estimate APOA5 contribution to HTG. We followed a recruit-by-genotype strategy to study a population composed of 44 individuals with high cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…SNPs in significant meQTLs were also associated with BMI, lipid traits, and glucose and insulin levels [ 35 ]. The meQTL at the APOA5 loci was confirmed by Oliva et al [ 53 ] using a candidate gene approach.…”
Section: Lipid-associated Methylation Quantitative Trait Loci and Regmentioning
confidence: 81%
See 1 more Smart Citation
“…SNPs in significant meQTLs were also associated with BMI, lipid traits, and glucose and insulin levels [ 35 ]. The meQTL at the APOA5 loci was confirmed by Oliva et al [ 53 ] using a candidate gene approach.…”
Section: Lipid-associated Methylation Quantitative Trait Loci and Regmentioning
confidence: 81%
“…A study by Bekkering et al [ 54 ] showed that the expression of lipid metabolism genes were altered after oxidized LDL exposure of monocytes. Methylation of CpG sites within exon 3 of APOA5 was positively correlated with triglyceride concentration and with a lipoprotein profile associated with atherogenic dyslipidemia [ 53 ]. Another candidate gene study reported decreased methylation levels of the actin-related protein 2/3 complex subunit 3 ( ARPC3 ) promoter-associated CpG site cg10738648 in both visceral adipose tissue and blood for carriers of the rs3759384 T allele in obese patients with hypertriglyceridemia, and showed ARPC3 expression to be correlated with plasma triglyceride levels [ 55 ].…”
Section: Lipid-associated Methylation Quantitative Trait Loci and Regmentioning
confidence: 99%
“…Therefore, carriers of the minor C allele of APOA5 rs651821 have different lipid properties in the gut compared with non-carriers, which may lead to alteration of gut microbiota composition as mentioned above [ 31 ], suggesting a role for microbiome pattern in the regulation of ApoA5. More interestingly, Oliva et al recently suggested that APOA5 genetic and epigenetic variabilities may jointly regulate circulating TG levels [ 35 ]; minor allele carriers of APOA5 SNPs (rs662799, rs3135506, and 724C > G) had significantly higher circulating TG levels (by an average of 57.5%) than non-carriers [ 35 ]. At the same time, APOA5 promoter and exon 3 were hypermethylated, whereas exon 2 was hypomethylated.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, APOA5 promoter and exon 3 were hypermethylated, whereas exon 2 was hypomethylated. In particular, exon 3 methylation was positively correlated with circulating TG levels and a lipoprotein profile linked to atherogenic dyslipidemia [ 35 ]. Taking these findings together, circulating TG levels were the highest in minor allele carriers of at least one APOA5 SNP, possibly together with a high methylation percentage in exon 3 (≥ 82%) among the population, which was not experimentally proven in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, for BUD13 , the genetic component is the sole contributor. For the APOA5 gene , which is located midway between AP006216.5 and BUD13 , there is suggestive genome-wide association resulting from both epigenetic and genetic components, which are not independent, and we find evidence for relationships between certain CpG PC s and SNP PC s. Notably, APOA5 is a known genetic determinant of TG variation, and recent data points to joint genetic and epigenetic regulation of TG [ 6 ].…”
Section: Discussionmentioning
confidence: 53%